Brand Ambassador, E-WOM, and Purchase Interest of Beauty Products Circulating in Indonesia (Study of Korean EXO Fans) - Saffanah, Cahya Dhiya; Widjayanti, Arifiani (Politeknik STIA LAN Jakarta, 2025)
This study aims to analyse the effect of brand ambassador Korean boy group EXO and e-WOM (electronic word of mouth) on purchase interest of beauty products circulating in Indonesia. The research was conducted among Korean EXO fans in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas. This study uses a quantitative approach with multiple linear regression analysis, with 160 samples for the survey. The results of this study indicate that brand ambassadors and e-WOM have a significant impact on purchase interest. This is shown by the F-test with the significance of brand ambassadors and e-WOM on purchase interest F = 80.182, sig. = 0.000 < 0.05. While the t-test shows the results of brand ambassador t = -8.091, sig = 0.000 <0.05 and e-WOM t = 12.546, sig = 0.000 <0.05, which means a significant effect. The coefficient of determination (R2) shows that the influence of brand ambassadors and e-WOM on purchase interest for beauty products is 50%. The remaining 50% is influenced by other factors. Keywords: brand ambassador; e-WOM; purchase interest; beauty products